2005
DOI: 10.1203/01.pdr.0000182591.46087.7d
|View full text |Cite
|
Sign up to set email alerts
|

NSE and S100 after Hypoxia in the Newborn Pig

Abstract: Perinatal asphyxia is an important cause of neonatal morbidity and mortality. There is the potential to halt cerebral damage if neural rescue strategies are applied within a short period of time after an insult. It is therefore important to be able to accurately identify neonates who may benefit from neural rescue therapies. Recent studies in asphyxiated neonates have correlated S100B and NSE with outcome; however, interpretation of these studies were difficult, as the timing of the measurements were not consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
2
13
1
2
Order By: Relevance
“…Therefore, we evaluated both TNF‐α and IL‐6 in the inflammatory response of the brain in this study. Because the half‐lives of S‐100β protein and NSE are different, we measured both of them in the present study to monitor the dynamic changes in brain damage 18‐21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we evaluated both TNF‐α and IL‐6 in the inflammatory response of the brain in this study. Because the half‐lives of S‐100β protein and NSE are different, we measured both of them in the present study to monitor the dynamic changes in brain damage 18‐21 …”
Section: Discussionmentioning
confidence: 99%
“…Because the half-lives of S-100β protein and NSE are different, we measured both of them in the present study to monitor the dynamic changes in brain damage. [18][19][20][21] Dexmedetomidine is a highly selective central α 2 -AR agonist. In addition to its sedative, analgesic, and anxiolytic effects, dexmedetomidine also protects brain tissue and has a significant neuroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of these altered metabolites, or biomarkers, might provide sensitive and specific information about severity of injury. Some potential markers such as neuron-specific enolase [13] and S100 [14,15] have been previously identified and are being investigated further, but it is important to continue searching for markers that can predict the timing and severity of the perinatal event and its neurologic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…They also argued that given a post‐partum increase in S100 with a reported half‐life ≤2 h in HIE newborns with brain disorders, the increased serum S100 level in HIE newborns could not be accounted for only from the S100 produced in the umbilical cord and placenta. Kecskes et al measured blood serum S100B at regular intervals in newborn piglets and reported that serum S100 protein levels in newborns at 48 and 72 h after birth were significantly higher in the severe HIE group than in the normal and lower HIE group 14 . They also noted a good correlation between serum S100B level and histopathological brain findings at 72 h after birth.…”
Section: Discussionmentioning
confidence: 99%